1995
DOI: 10.1002/hep.1840220117
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bolus injections and continuous infusions of somatostatin and placebo in patients with cirrhosis: A double-blind hemodynamic investigation

Abstract: The present double-blind study was aimed at investigating the hemodynamic and humoral effects of somatostatin or placebo in patients with cirrhosis. Patients were randomly assigned to receive either an injection of 250 micrograms of somatostatin followed by a constant infusion of somatostatin at 250 micrograms/h (n = 13), an injection of 250 micrograms of somatostatin followed by a 500 micrograms/h continuous infusion (n = 10), or an injection of placebo followed by a placebo infusion (n = 9). Placebo had no e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
76
2
5

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 31 publications
9
76
2
5
Order By: Relevance
“…6 In this study, we found that SST but not OCT effectively prevented the increase in WHVP with simultaneous increase in FHVP achieving an almost unchanged portal pressure. This is consistent with the findings of Cirera et al, 31 where the recorded reduction in the HVPG after the administration of SST was attributed to a significant decline in WHVP accompanied by a marked increase in FHVP. Although both SST and OCT inhibit the secretion of glucagon through binding with SST receptors 2, their different effects on splanchnic haemodynamics suggest involvement of other mechanisms.…”
Section: Discussionsupporting
confidence: 93%
“…6 In this study, we found that SST but not OCT effectively prevented the increase in WHVP with simultaneous increase in FHVP achieving an almost unchanged portal pressure. This is consistent with the findings of Cirera et al, 31 where the recorded reduction in the HVPG after the administration of SST was attributed to a significant decline in WHVP accompanied by a marked increase in FHVP. Although both SST and OCT inhibit the secretion of glucagon through binding with SST receptors 2, their different effects on splanchnic haemodynamics suggest involvement of other mechanisms.…”
Section: Discussionsupporting
confidence: 93%
“…[6][7][8]10,12,13 It has been demonstrated that bolus injections of SMT cause a rapid and more pronounced reduction of portal pressure and azygos blood flow than those observed with continuous infusion. 26 These marked hemodynamic effects may explain, at least in part, the higher efficacy reported in clinical trials using additional boluses. However, the present study clearly shows that the combination of Abbreviation: PSTV, transient paroxysmal supraventricular tachycardia.…”
Section: Discussionmentioning
confidence: 99%
“…However, exact mechanism of the action remains unknown. In a double-blind, placebo-controlled hemodynamic study, Cirera et al (1995) demonstrated that a bolus injection of SMT caused a rapid decrease in portal pressure gradient (52%) and azygos blood flow (45%). Vanheule et al (2008) suggested that the very rapid onset effect of SMT is indicative of a direct action involving the vascular smooth muscle cell.…”
Section: Discussionmentioning
confidence: 99%
“…Somatostatin (SMT) has been proposed as a treatment for variceal gastrointestinal bleeding because of its ability to decrease portal pressure without significant adverse systemic effects. The effect of somatostatin is possibly mediated through its ability to cause a splanchnic vasoconstriction and reduction of splanchnic blood flow (Carsson et al, 1994;Cerini et al, 1998;Cirera et al, 1995;Jenkins et al, 1998;Saruc et al, 2003;Sonnenberg et al, 1981). To our knowledge there are no data on the use of SMT in traumatic intra-abdominal hemorrhages.…”
Section: Introductionmentioning
confidence: 99%